The Election System of the Swiss Confederation: Counting of Votes and Establishment of Election Results - M. A. Tarnavskaya (Vestnik MGIMO-Universiteta, 2014)
In the following article the author covers the process of counting the votes and the disclosure rules of establishment the election results in the Swiss Confederation. Switzerland along with other EU member states pays special attention to the determination of the election results. According to Art. 149 para. 2 Federal Constitution of the Swiss Confederation the elections to the National Council, which is one of two chambers of the Federal Assembly, are held according to proportional representation system. The Hagenbach-Bischoff system is used for allocating seats in National Council of the Swiss Con federation. However the above mentioned system for determining the quota of votes per each mandate creates ambiguous opinions among Swiss scientists and legal experts, which frequently comes up in discussions whether to modify it or not. In this article, the author also gives a brief description of the main political parties in Switzerland and statistics of seats allocation in 49 legislature of National Council following the elections of October 23, 2011. As a result, the author provides the full information on the process of votes counting and establishment of election results in the Swiss Confederation. The material presented in this article is particularly interesting and relevant in terms of improving the electoral legislation in the Russian Federation. The information presented by the author will be useful to all parties interested in electoral law.